Analisis Kesiapan Pengembangan Rekam Medis Elektronik Menggunakan DOQ-IT di RS “X” Yogyakarta - Kori Puspita Ningsih; Suryo Nugroho Markus; Ngatoiatu Rahmani; Ida Nursanti (Lembaga Penerbitan Universitas Esa Unggul, 2023)
AbstractMedical records are a vital part of the evidence for recording patient examinations. Several middle and high-income countries have implemented Electronic Medical Records (RME) to support patient health documentation. The development of RME in Indonesia has been regulated in the Minister of Health Regulation 24 of 2022. Hospital